2012
DOI: 10.4100/jhse.2012.72.01
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different standards of opponents on observed player performance in the English Premier League

Abstract: Redwood-Brown A, Bussell C, Bharaj HS. The impact of different standards of opponents on observed player performance in the English Premier League. J. Hum. Sport Exerc. Vol. 7, No. 2, pp. 341-355, 2012. The purpose of the investigation was to develop an understanding of how the performance of a soccer team is affected when playing against different standards of opponents in the English Premier League. Twenty-nine Premier League matches were analysed during the 2010-2011 season for 18 selected performance indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Sin embargo, estas posiciones han mostrado requerir mejores capacidades físicas según los resultados evaluados usando los test de carrera intermitentes 5 . Además, los jugadores relativos a las posiciones de mediocentro y lateral defensivo desarrollan y completan mayor cantidad de pases comparados con otras posiciones 34 .…”
Section: Acciones Según El Puesto Específicounclassified
“…Sin embargo, estas posiciones han mostrado requerir mejores capacidades físicas según los resultados evaluados usando los test de carrera intermitentes 5 . Además, los jugadores relativos a las posiciones de mediocentro y lateral defensivo desarrollan y completan mayor cantidad de pases comparados con otras posiciones 34 .…”
Section: Acciones Según El Puesto Específicounclassified
“…The current study was not able to present individual players data with regards to the impact of score line however previous work using a case study approach of one team has found that players differ in their approach to different score line states. 20 To achieve maximum success, it may therefore be more appropriate, that to maximize team performance, the starting eleven should be picked based on the external factors highlighted to influence player performance, for example, if playing against top opposition it may be more appropriate to select players who perform better against higher abilities, or in a negative score line states.…”
Section: Directionsmentioning
confidence: 99%
“…A secondary issue has been the technological barriers in data collection methods that have limited the ability to generalize findings for both physical and technical performance investigated. Categorizing players by position (defenders, midfielders, attackers) in relation to score line effects has been considered for activity profiles but only using very small data sets or single clubs using overall match status (winning, drawing, losing) rather than by how much the team were winning or losing by. There is however, a need to investigate score line effects on performance using a greater volume of data as well as objective and reliable methods.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, central midfielders and full backs perform and complete more passes compared to other positions (Redwood-Brown, Bussell, & Bharaj, 2012;Taylor, Mellalieu, & James, 2004). Given the evolutionary changes highlighted previously in elite soccer match-play (Barnes et al, 2014;Wallace & Norton, 2014), it would be of interest to track longitudinal positional changes to gain insight into physical and technical requirements of modern players.…”
Section: Introductionmentioning
confidence: 99%